HUBUNGAN TAYANGAN KEKERASAN DI TELEVISI DENGAN PRESTASI BELAJAR SISWA DI SEKOLAH DASAR - Mandasari, Dewi Septiani (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
Each learning process will result in changes in the behavior of students who experience the process. For students in school schools, this moral and social coaching can be done through formal study, as well as elements that can continue and develop the soul and developing soul and spirit and value value 1945 to the younger generation should be improved in the curriculum and community environment. There are many things that can result in a child behaving to imitate what he has seen or seen. One of them is the violence in electronic or television media. Impressions of violence in teleisi can directly affect a child's behavior to imitate him because the child does not yet know what he or she is seeing is true or false. The hypothesis of this research is "The correlation between the teleisi violence with the achievement of student learning in the student's school in SDN Lerpak 3 Kecamatan Geger Kabupaten Bangkalan" The method used is the method of documentation, observation and questionnaire that support both variables. So to find the proposed hypothesis accepted or rejected then use rumus correlation poduct moment. In the results of the data count can be seen that t= count 2,88 whereas according to the significant level 5%=2,04 and 1%=2,75 Thus the value of t arithmetic greater than t table at a significant level 5% so that the working hypothesis (Ha) is acceptable, while the null hypothesis (Ho) is rejected means that there is a connection of teleisi teleisi impression with the achievement of students in primary school.